Occurrence, biology, natural enemies and management of Tuta absoluta in Africa - Mansour, R.; Brévault, T.; Chailleux, A.; Cherif, A.; Grissa-Lebdi, K.; Haddi, K.; Mohamed, S.A.; Nofemela, R.S.; Oke, A.; Sylla, S.; Tonnang, Henri E.Z.; Zappalà, L.; et al. (Schweizerbart, 2018)
The South American tomato pinworm, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), is a devastating invasive pest of tomato crops in several areas around the world including Africa. Here, we comprehensively review and discuss the relevant scientific knowledge on its occurrence, biological and ecological aspects, fortuitous insect natural enemies, and potential advantages and constraints of pest management scenarios adopted against this pest in tomato crops in both Northern and Sub-Saharan Africa. We conclude the manuscript with a comprehensive research agenda providing future priorities towards sustainable control of this important tomato pest.